IoT-Based Smart Booking of Electric Vehicle Charging Station - R, Gowtham; P, Guganesh; V, Ilanchelvan Harikumar; K, Ramachandran; C, Udhaya Kumar; A, Priyadharshini (Journal of ISMAC, 2023)
The Immense growth in the implementation of electric vehicles (EVs), has established a path in the advancements of charging infrastructure. Interlinking and connecting the charging stations to a common server is essential for future EV adoption, and this can reduce the user's anxiety. The existing charging stations have not implemented charging slot availability and time scheduling management. The objective of this research is to enhance the current electric vehicle (EV) charging infrastructure by gathering and sharing real-time information about the availability of reserve slots at charging stations. This information is made available to users through an interactive application created with Android Studio, allowing them to locate the closest charging station for their EV. The application utilizes the State of Charge of the EV to assign available charging slots. The proposed real-time predictive charging server infrastructure avoids latency, effectively manages time scheduling, and avoids draining electric vehicle batteries. This proposed system uses the real-time traffic database to estimate the minimum distance path to reach the charging station.
Keywords: Internet of Things; Firebase; State of Charge; Electric Vehicle; Application